COLLOIDS VERSUS CRYSTALLOIDS GUIDED BY INFERIOR VENA CAVA COLLAPSIBILITY INDEX IN BIPOLAR TRANSURETHRAL RESECTION PROSTATE; RANDOMIZED CONTROLLED STUDY. - Mohamed Ahmed Tolba; Mohamed Abdellatif Ghanem; Mohammed Abaalkhayl; Sameh Mohamed El-Sherbiny; Amany Hazem EL-Deeb (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
BACKGROUNDː Intravenous (IV) fluid replacement during transurethral resection of the prostate (TURP) is still unclear. The purpose of this study was to compare colloids versus crystalloids using inferior vena cava collapsibility index (IVC-CI) to show their impact on the total amount of IV infused fluids. Methods: This study included 34 American Society of Anesthesiologists physical status class I and II patients who underwent bipolar TURP. Eligible patients were randomly assigned to two equal groups, crystalloid and colloid (n=17 in each group). The study subjects and the investigators assessing the outcome were blinded to the study group. The primary outcome was the total IV administered fluids volume. Secondary outcomes were the postoperative serum sodium and potassium, maximum and minimum IVC diameters, IVC-CI, incidence of bradycardia and hypotension, and total IV furosemide dose RESULTSːI The mean ± SD of the total intravenous infused fluids in colloid group was 355.6 + 151 ml and in the crystalloid group was 602.5 + 200 ml (p = 0.0003). There were no statistical difference between the 2 groups in the serum sodium and potassium at the end of surgery, maximum and minimum IVC diameters, IVC-CI, incidence of bradycardia, incidence of hypotension, total intraoperative ephedrine dose, incidence of intraoperative nausea and/or vomiting, and total IV furosemide dose. CONCLUSIONSː Colloid volume optimization using US-guided IVC-CI had reduced the total IV fluid volume and achieved volume optimization during TURP surgery with hemodynamic stability preventing fluid overload.